Revolutionizing Medical Education Through Digital Technologies - Muhammad Nadim Akbar Khan; Saadia Sultana; Noor-Mah Khan (Journal of Islamic International Medical College, 2024)
Digital technologies are electronic tools, systems, processes, devices, and resources that generate, store, or process data. Common examples are websites, video streaming, e- books, blogs, virtual patients, social media platforms (Facebook, Twitter, and Instagram), tools (personal computers, smart phones, tablets) and education-specific devices (data projectors, multimedia, simulators, digital cameras, digital stethoscopes, and laparoscopic simulators).